Commercial production of oil from oil shale and possible changes in the world oil market configuration - T. V. Polyakova (Vestnik MGIMO-Universiteta)
The world oil market is changing rapidly, there rises a new global center of world oil production – North America, which production opportunities are estimated by experts as outperforming those of Middle East. This is made possible thanks to inception of commercial oil production from oil shale in North America. The article deals with the problems and prospects of the development of shale oil in the U.S. and the impact of the growth of its production on the configuration of the world oil market.